2014
DOI: 10.2139/ssrn.2383795
|View full text |Cite
|
Sign up to set email alerts
|

College Wage Premium Over Time: Trends in Europe in the Last 15 Years

Abstract: While there has been intense debate in the empirical literature over the evolution of the college wage premium in the United States, its evolution in Europe has received little attention. This paper investigates the causes of the evolution of the college wage premium in 12 european countries from 1994 to 2009. I use cross country variation in relative supply, demand, and labour market institutions to examine their effects on the trend in wage inequality. I address possible concerns of endogeneity of the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
(12 reference statements)
3
17
0
Order By: Relevance
“…After all, we are just comparing two economic variables: the college wage premium and supply of college graduates in the U.S. workforce. But a host of rigorous studies commencing with Katz and Murphy (31) confirm the remarkable explanatory power of this simple supply-demand framework for explaining trends in the college-versus-high-school earnings gap over the course of nine decades of U.S. history, as well as across other industrialized economies (most notably, the United Kingdom and Canada), and among age and education groups within countries (19,(31)(32)(33)(34)(35)(36). It also bears emphasis that the U.S. was far from the only Western country to experience this surge.…”
Section: Bringing the Supply-demand Framework To The Datamentioning
confidence: 95%
“…After all, we are just comparing two economic variables: the college wage premium and supply of college graduates in the U.S. workforce. But a host of rigorous studies commencing with Katz and Murphy (31) confirm the remarkable explanatory power of this simple supply-demand framework for explaining trends in the college-versus-high-school earnings gap over the course of nine decades of U.S. history, as well as across other industrialized economies (most notably, the United Kingdom and Canada), and among age and education groups within countries (19,(31)(32)(33)(34)(35)(36). It also bears emphasis that the U.S. was far from the only Western country to experience this surge.…”
Section: Bringing the Supply-demand Framework To The Datamentioning
confidence: 95%
“…We present the clearing market conditions and the full equilibrium system in the Appendices B and C respectively. 17…”
Section: Decentralized Competitive Equilibrium (Dce)mentioning
confidence: 99%
“…for the value of skill premium which is consistent with the data. 19 Our 21 We set public debt to GDP ratio in the status quo economy equal to 1 9 The value of the skill premium typically ranges from 1.45 to 1.80 depending on the country, timeframe and method of measurement (for an overview of inequality measures see Krueger et al (2008) while for measurement issues see Crivellaro (2016) and OECD Education at a Glance reports (2008-2018)). For our target value we use OECD's Relative Earnings by educational attainment indicator.…”
Section: Parameter Values and …Scal Policy Datamentioning
confidence: 99%
“…This implies that the economic efficiency of labour markets is reduced by different policies writ large. Indeed, some comparative studies have found that labour market regulations or union strength are associated with lower education premiums (Crivellaro 2014;Hanushek et al 2015;Katz et al 1995), while others find no effect of labour market institutions (van der Velden and Bijlsma 2016). Acemoglu (2002) develops a theoretical argument that labour market institutions are crucial because they affect the direction of technological change: European firms, operating in densely regulated labour markets, have more incentives to raise low-skilled workers' productivity, therefore technological change is less skill-biased compared to the US.…”
Section: Returns To Education Inequality and Policymentioning
confidence: 99%